Accelerated oxidation in ductile refractory high-entropy alloys. (June 2018) - Sheikh, Saad; Bijaksana, Muhammad Kurnia; Motallebzadeh, Amir; Shafeie, Samrand; Lozinko, Adrianna; Gan, Lu; Tsao, Te-Kang; Klement, Uta; Canadinc, Demircan; Murakami, Hideyuki; Guo, Sheng
Abstract: Refractory high-entropy alloys (RHEAs) are promising candidates for new-generation high temperature materials, but they generally suffer from room temperature brittleness and unsatisfactory high-temperature oxidation resistance. There currently lack efforts to address to these two critical issues for RHEAs at the same time. In this work, the high temperature oxidation resistance of a previously identified ductile Hf0.5 Nb0.5 Ta0.5 Ti1.5 Zr RHEA is studied. An accelerated oxidation or more specifically, pesting, in the temperature range of 600–1000 °C is observed for the target RHEA, where the oxidation leads the material to catastrophically disintegrate into powders. The pesting mechanism is studied here, and is attributed to the failure in forming protective oxide scales accompanied by the accelerated internal oxidation. The simultaneous removal of zirconium and hafnium can eliminate the pesting phenomenon in the alloy. It is believed that pesting can also occur to other equiatomic and non-equiatomic quinary Hf-Nb-Ta-Ti-Zr or quaternary Hf-Nb-Ti-Zr and Hf-Ta-Ti-Zr RHEAs, where all currently available ductile RHEAs are identified. Therefore, the results from this work will provide crucial perspectives to the further development of RHEAs as novel high-temperature materials, with balanced room-temperature ductility and high-temperature oxidation resistance. Graphical abstract: Highlights: High temperature oxidation resistance of Hf0.5 Nb0.5 Ta0.5 Ti1.5 Zr RHEA is studied. Pesting in the temperature range of 600–1000 °C is observed. Pesting leads the material to catastrophically disintegrate into powders. Pesting due to not forming protective oxide scales & accelerated internal oxidation. Simultaneous removal of zirconium and hafnium can eliminate pesting.